Implementation of Contextual-Based Chemistry Electronic Textbook Class X SMA/MA Semester II on Learning Outcomes and Student’s Learning Motivation - Khairani Islamiyah; Tita Juwitaningsih; Saronom Silaban (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Low results study students and motivation student in learning chemistry during the Covid-19 pandemic at Baitul Aziz Private High School Deli Serdang. This research aim for knowing outcomes learning students who are taught with contextual-based chemistry electronic textbook more high from score criteria minimum completeness (KKM = 75); knowing student’s learning motivation who are taught with contextual-based chemistry electronic textbook. This research using the ADDIE model (Analysis; Design; Development; Implementation; Evaluation) in the article this will discussed at the implementation. Population in study this is is student class X MIPA Baitul Aziz Private Senior High School Deli Serdang 2021/2022 as many as 50 students, sample study this student class X MIPA2 Baitul Aziz Deli Serdang Private High School as many as 24 people were selected with using purposive sampling technique. Instruments used in research including: instruments test as many as 10 essay questions and questionnaires motivation study students. Research results show that results study student higher from KKM value (test one sample t-test obtained result value sig. α = 0.002 0.05; score tcount ttable = 8.087 1.714) and students motivated (81.7%) to study chemical with use contextual-based chemistry electronic textbook very effective used in learning chemistry at school to improve learning outcomes and student’s learning motivation.